THE FEATURES OF LASER EMISSION ENERGY DISTRIBUTION AT MATHEMATIC MODELING OF WORKING PROCESS - A. M. Avsiyevich; O. G. Devoino; A. D. Kocherov; A. P. Pilipchuk (Наука и техника)
The space laser emission energy distribution of different continuous operation settings depends from many factors, first on the settings design. For more accurate describing of multimode laser emission energy distribution intensity the experimental and theoretic model, which based on experimental laser emission distribution shift presentation with given accuracy rating in superposition basic function form, is proposed. This model provides the approximation error only 2,2 percent as compared with 24,6 % and 61 % for uniform and Gauss approximation accordingly. The proposed model usage lets more accurate take into consideration the laser emission and working surface interaction peculiarity, increases temperature fields calculation accuracy for mathematic modeling of laser treatment processes. The method of experimental laser emission energy distribution studying for given source and mathematic apparatus for calculation of laser emission energy distribution intensity parameters depended from the distance in radial direction on surface heating zone are shown.